(untitled) (Revista Latino-Americana de Enfermagem, 2009)
This quantitative, cross-sectional study was performed to estimate the difference between the perceived norms among university students, based on a survey of 196 nursing students from Lima, Peru. A questionnaire was used to measure the students' perception about drug use and their actual use. Descriptive statistical analysis was performed, considering a value greater, smaller or equal to 10 to establish the difference. The perceived norms for alcohol and tobacco were above 50%, against 6% for marijuana and cocaine; with 57.7% of participants reporting tobacco use, 84.7% alcohol, 2.6% marijuana and 1% cocaine. Marijuana and cocaine use was overestimated, while alcohol use was underestimated. The perception of tobacco use was correct. The study findings are useful to sensitize university authorities and put prevention policies in practice.